A comprehensive review on the effects of engineered nanoparticles on microalgal treatment of pollutants from wastewater. (10th April 2022) - Xiong, Jiu-Qiang; Cui, Pengfei; Ru, Shaoguo; Kurade, Mayur B.; Patil, Swapnil M.; Yadav, Krishna K.; Fallatah, Ahmed M.; Cabral-Pinto, Marina M.S.; Jeon, Byong-Hun
Abstract: Engineered nanoparticles (ENPs) are advanced, high-throughput materials that have revolutionized almost every aspect of human life over the past decade with its numerous commercial applications across the globe. However, these particles have made their way into the environment through various pathways, eliciting unintended environmental consequences, and endangered various ecosystems and human health. Microalgae and their related microbial communities act as one of the key indicators of nano-toxicity, and play essential roles in bioremediation and bioenergy productions. In this review, we analyzed the interactions of nanoparticles with microalgae and the associated microbial communities along with its influence on the remediation capacities of pollutants such as organic pollutants, nitrogen and phosphorus. We also provide a comprehensive insight into the transcriptomics, proteomics and metagenomics of ENPs influenced microalgae and their related microbial communities to identify the in-depth protective and metabolic mechanisms. The information provided herein can extend the understanding of the effect of nanoparticles on environmental processes and might be useful in designing its disposal and treatment strategies.